THE ROLE OF SOCIAL COMPETENCE IN THE PROFESSIONAL ACTIVITY OF FUTURE EDUCATORS OF PRESCHOOL EDUCATIONAL INSTITUTIONS - Xalilova Dilnoza Furqatovna (Web of Journals Publishing, 2024)
The article discusses the importance of social and professional competencies for the implementation of the priority direction of preschool education - socialization; the problem of establishing social relationships with parents, students and teaching staff; a list of competencies that ensure this inclusion; grounds for creating the necessary direction for this.
Keywords: Competence, social competence, pedagogical conditions, future preschool educator, pedagogical competence, personal and professional self-determination.